Flexural Behavior of RC Slabs Strengthened in Flexure with Basalt Fabric-Reinforced Cementitious Matrix - Sugyu Lee; Kinam Hong; Yeongmo Yeon; Kyusan Jung (Advances in Materials Science and Engineering)
This paper presents both experimental and analytical research results for predicting the flexural capacity of reinforced concrete (RC) slabs strengthened in flexure with basalt fabric-reinforced cementitious matrix (FRCM). A total of 13 specimens were fabricated to evaluate the flexural behavior of RC slabs strengthened with basalt FRCM composite and were tested under four-point loading. The fiber type, tensile reinforcement ratio, and the number of fabric layers were chosen as experimental variables. The maximum load of FRCM-strengthened specimens increased from 11.2% to 98.2% relative to the reference specimens. The energy ratio and ductility of the FRCM-strengthened specimens decreased with the higher amount of fabric and tensile reinforcement. The effective stress level of FRCM fabric can be accurately predicted by a bond strength of ACI 549 and Jung’s model.